2008
DOI: 10.1007/s12615-008-9003-z
|View full text |Cite
|
Sign up to set email alerts
|

Análisis experimental de los rangos de movilidad articular y fuerza muscular requerida para la conducción de vehículos automóviles

Abstract: Annex III of Directive 2006/126/CE related to driving license procedure describe the minimum health criteria necessary for obtaining or renewal the driving license. If we focus our analysis in the musculoskeletal assessment procedure we can appreciate that there hasn't been the same scientific and technological progression as other technical aids (Directive 2000/56/CE). This paper shows the results of a research program based on the definition of the joint mobility range and muscular strength done during drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…From a quantitative point of view, the results showed that, in roundabouts and obstacle avoidance manoeuvres (slalom), the maximum values for steering wheel force obtained reached 24.2 N. In the case of braking tests, the maximum values ranged between 85.6 and 137.5 N, very close to the expected values according to previous investigations carried out by other research teams [11][12][13][14].…”
Section: Discussionsupporting
confidence: 81%
“…From a quantitative point of view, the results showed that, in roundabouts and obstacle avoidance manoeuvres (slalom), the maximum values for steering wheel force obtained reached 24.2 N. In the case of braking tests, the maximum values ranged between 85.6 and 137.5 N, very close to the expected values according to previous investigations carried out by other research teams [11][12][13][14].…”
Section: Discussionsupporting
confidence: 81%